Studi Fenomenologi Pengalaman Ibu dalam Merawat Anak Stunting Usia 6 – 24 Bulan Berbasis Health Belief Model - Fathmy Fitriany Soulissa; Yuni Sufyanti Arief; Ririn Probowati (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the phenomenological description of the experiences of mothers caring for children with stunting at the age of 6-24 months. The method used is qualitative with a phenomenological study design in mothers who care for children with stunting aged 6-24 months, with 15 participants selected by purposive sampling. The results showed that there were four main themes related to the experience of mothers caring for children with stunting aged 6-24 months, namely exclusive breastfeeding, the inappropriateness of MP-ASI giving, lack of mother's knowledge and non-fluent breastfeeding. In conclusion, the mother's experience in caring for stunted children, namely exclusive breastfeeding is incomplete, breastfeeding is replaced by Sufor, early MP-ASI giving, inappropriateness in giving MP-ASI, lack of knowledge of mothers about child growth, child nutrition and the importance of exclusive breastfeeding and non-current breastfeeding caused by heredity and only a little out. Keywords: Children, Health Belief Model, Mother, Behavior, Stunting